2023
DOI: 10.1101/2023.01.31.526423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A general strategy to develop fluorogenic polymethine dyes for bioimaging

Abstract: Fluorescence imaging is an invaluable tool to study biological processes and further progress depends on the development of advanced probes. Fluorogenic dyes are crucial to reach intracellular targets and label them with high specificity. Excellent fluorogenic rhodamine dyes have been reported, but they often require a long and low-yielding synthesis and are spectrally limited to the visible range. Here, we present a general strategy to transform polymethine compounds into fluorogenic dyes using an intramolecu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Additional modifications to both the cyanine and the HaloTag protein may enhance binding properties, fluorogenicity, and photostability of the protein-small molecule pairs. We believe the efficient cyanine-based self labeling tags reported here and in recent studies by Rivera-Fuentes and coworkers will provide a long-wavelength NIR channel for multicolor experiments and, perhaps, improved imaging resolution in complex tissue settings …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Additional modifications to both the cyanine and the HaloTag protein may enhance binding properties, fluorogenicity, and photostability of the protein-small molecule pairs. We believe the efficient cyanine-based self labeling tags reported here and in recent studies by Rivera-Fuentes and coworkers will provide a long-wavelength NIR channel for multicolor experiments and, perhaps, improved imaging resolution in complex tissue settings …”
Section: Discussionmentioning
confidence: 60%
“…We believe the efficient cyanine-based self labeling tags reported here and in recent studies by Rivera-Fuentes and coworkers will provide a long-wavelength NIR channel for multicolor experiments and, perhaps, improved imaging resolution in complex tissue settings. 84 Finally, these studies illustrate the potential for dynamic ringopen/ring-closed chemistry with heptamethine indocyanines, which may enable the discovery for a range of long-wavelength optical probes. The prospect for such efforts is heightened by prior studies on rhodamines, fluoresceins, and rhodols, where a range of fluorogenic sensors and imaging strategies have been developed by taking advantage of nonfluorescent lactone, fluorescent zwitterion equilibria.…”
Section: ■ Conclusionmentioning
confidence: 87%
“…Notably, the Rivera-Fuentes group has successfully developed spontaneously blinking polymethine dyes (Figure 9). [37] Secondly, researchers should explore new mechanisms beyond spirocyclization to enable spontaneous blinking. The Urano group demonstrated that spontaneous blinking can be achieved through a reversible nucleophilic reaction between intracellular glutathione and a xanthene-based fluorophore in the ground state (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Probes typically consist of three parts: an active drug molecule; a linker; and a reporting label [28]. According to the different reporting labels, the probes are divided into immobilized (solid-phase carriers as report label) [29] and active probes (biotin [30] and fluorescent groups [31] (Figure 3), bio-orthogonal reaction groups [32], and photoaffinity reaction groups [33] as reporting labels). Immobilized probes are a classic tool for target identification.…”
Section: Application Of Protacs In Target Identificationmentioning
confidence: 99%